1995
DOI: 10.1021/ma00126a033
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence from Substituted Poly(thiophenes): From Blue to Near-Infrared

Abstract: We report a systematic approach to the control of the conjugation length along the poly-(thiophene) backbone. The planarity of the main chain can be permanently modified by altering the pattern of substitution and character of the substituents on the poly(thiophene) chain, and the conjugation length is thus modified. We obtain blue, green, orange, red, and near-infrared electroluminescence from four chemically distinct poly(thiophenes). The external quantum efficiencies are in the range of 0.01-0.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
169
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(177 citation statements)
references
References 12 publications
4
169
1
Order By: Relevance
“…15 Intramolecular SHE may reduce the π-orbital overlap between two adjacent units and lead to undesirable hypochromatic shifted absorption spectra and wide bandgap (E g ), 10,16−20 however, as is well-known, wide absorption spectra, and narrow E g of the absorber are crucial for organic solar cells (OSCs) application. 21 Although SHE has been considered as a negative effect for polymer's self-aggregation and effective conjugation, one advantage should be pointed out, that is, SHE can significantly decrease the highest occupied molecular orbital (HOMO) energy levels of the polymer.…”
Section: −5mentioning
confidence: 99%
See 2 more Smart Citations
“…15 Intramolecular SHE may reduce the π-orbital overlap between two adjacent units and lead to undesirable hypochromatic shifted absorption spectra and wide bandgap (E g ), 10,16−20 however, as is well-known, wide absorption spectra, and narrow E g of the absorber are crucial for organic solar cells (OSCs) application. 21 Although SHE has been considered as a negative effect for polymer's self-aggregation and effective conjugation, one advantage should be pointed out, that is, SHE can significantly decrease the highest occupied molecular orbital (HOMO) energy levels of the polymer.…”
Section: −5mentioning
confidence: 99%
“…For example, poly(3-cyclohexylthiophene) (P3chT) exhibited more twisted conjugating backbone than poly(3-hexylthiophene) (P3hT) because of stronger SHE of cyclohexyl than hexyl, which resulted in a larger dihedral angle (θ) between the two adjacent thiophene rings together with a wider E g and a deeper lying HOMO of −5.72 eV, 0.72 eV lower than that of P3hT (−5.0 eV) experimentally. 10 Theoretically, Bredas and co-workers reported that the ionic potential of the polythiophene increased gradually as the torsion angle increased from 0 to 90°. 22 This will be very interesting for OSCs application, which is composed of a polymeric donor and a fullerene acceptor, and the deeper lying HOMO of the polymer donor will be beneficial for higher open-circuit voltage (V oc ).…”
Section: −5mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been tremendous interest in conjugated polymer technology for various applications. Among conjugated polymers, polythiophenes exhibit some unique advantages for developing optoelectronic devices [1][2][3][4][5][6][7], for instance, they have been widely used in solution-processed polymer solar cells [8,9] and polymer field-effect transistors [10], as well as light-emitting diodes [11]. Substituted polythiophenes can be tailored for various applications by designing the side groups to give the polymer different desired properties.…”
Section: Introductionmentioning
confidence: 99%
“…11 Imposing steric hindrance through bulky side groups is one way to tune color by distorting a conjugation chain. 6,7,12 This approach, however, gives rise to bringing emission from the more conjugated segments. Another way is to incorporate nonconjugated segments such as silylene, methylene, and ether groups into a conjugated backbone.…”
Section: Introductionmentioning
confidence: 99%